"Formation of Legal Awareness and Legal Culture in Youth: A Priority Direction of the Education System" - Utaev Gayrat Gaybullaevich; Botirov Sarvar Bahrom ugli (Open Academia, 2025)
This article focuses on the necessity of conducting specific scientific research on elevating the legal awareness, legal culture, and public oversight to a new level, especially in terms of effectively utilizing these tools in the fight against corruption. It emphasizes the need to prioritize this issue within the framework of the state's policy
Keywords: legal awareness; legal culture; public oversight; legal literacy